The Influence of Motivation, Communication and Job Stress on Employee - Olla Meldi Wasyifa; Dea Riskika Mulyani; Pasika Utami; Riyanti Ratnasari; Satriadi Satriadi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to analyze and understand the impact of motivation, communication and work stress on employee job satisfaction. This study was conducted through a comprehensive literature review of previous research on the topic. The literature review is analyzed and summarized to produce conclusions that can. that a positive work environment, effective communication, and high levels of motivation are key factors in increasing employee job satisfaction. This study provides practical implications for organizations to increase employee job satisfaction by focusing on these factors. This research has a significant contribution to the development of theory and practical understanding in human resource management